Prevalence and impact of mistreatment on academic motivation among clinical year medical students in Thailand - Tanrin Hiranwong; Nahathai Wongpakaran; Patipan Sitthiprawiat; Sirinut Siritikul; Jiraphat Jiwtrakul; Sirilux Klaychaiya; Pookit Chaipinchana; Pimolpun Kuntawong; Athavudh Deesomchok; Danny Wedding; Tinakon Wongpakaran (Scientific Reports)
Abstract Mistreatment can adversely affect students’ academic performance and mental health. This study investigated the prevalence of mistreatment and its association with academic motivation among Thai clinical-year medical students. A cross-sectional study was conducted among medical students throughout Thailand using the Composite Questionnaire of Mistreatment and Academic Motivation Scale (AMS). Descriptive statistics, chi-square tests, correlations, and regression analyses were conducted. A p value < 0.05 was considered statistically significant. The sample included 399 students, with a median age of 23 years (interquartile range [IQR]: 22–24), and 61.5% were female. A total of 81% of participants experienced mistreatment. Twenty-nine percent of students thought that mistreatment occurred because the maltreaters did not consider mistreatment as inappropriate or serious. Students who experienced mistreatment exhibited lower AMS (B =  − 9.16, 95% CI − 15.37 to − 2.95, p value = 0.004) than those who did not. Moreover, students who experienced academic mistreatment exhibited a higher amotivation score (B = 1.50, 95% CI 0.16 to 2.85, p value = 0.029) than those who did not. The prevalence of mistreatment was unexpectedly high, and it was associated with students’ motivation to study. Educational institutions should prioritize addressing this issue and developing strategies to provide assistance, including enhancing reporting systems.